The Ultimate Empath - Srinivas, Tara (Ars Medica, 2025)
"the ultimate Empath" is an exploration of the practice of medicine as a healing art, one that involves caring for, making whole, and developing a connection between patient and provider that not only implements science but also respects culture, customs, and identity. Expression of identity -- particularly from the viewpoint of a student provider -- with regard to empathy for patient presentations, is explored.